2012
DOI: 10.5455/medarh.2012.66.336-339
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Disease Biomarkers Activity and Immunophenotyping as Important Factors in SLE Clinical Management

Abstract: The highly specific biomarkers for monitoring of SLE disease activity are not yet defined up to date, due to existing of different clinical SLE phenotypes caused by individual genetic variation. Basically, numerous clinical complications follow SLE patients such as nephritis, atherosclerosis and cardial, CNS, gastrointestinal and ophthalmological complications, as well. Their monitoring in clinical SLE management can be evaluated by analysing of specific biochemical parameters and require permanent clinical ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Serum concentrations of anti-dsDNA, C3, and C4 are key serological markers that correlate with disease activity in SLE. 33,34 We observed a trend that SRI(4) response was associated with a reduction in anti-dsDNA. However, no differences in changes from baseline in C3 and C4 complement concentrations between responders and nonresponders were observed.…”
Section: Discussionmentioning
confidence: 75%
“…Serum concentrations of anti-dsDNA, C3, and C4 are key serological markers that correlate with disease activity in SLE. 33,34 We observed a trend that SRI(4) response was associated with a reduction in anti-dsDNA. However, no differences in changes from baseline in C3 and C4 complement concentrations between responders and nonresponders were observed.…”
Section: Discussionmentioning
confidence: 75%
“…Immuno-phenotyping has proven to be a very useful tool in the identification, monitoring and management of various clinical diseases [ 9 11 ]. Although recent publications have sought to develop in depth multicolour flow cytometric panels for the accurate delineation of various lymphocyte populations and subpopulations (including B cells) during immunodeficiencies [ 12 , 13 ], very few studies exist that specifically assess immune-phenotypic change during active Mycobacterium tuberculosis infection [ 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subasic et al (2012) showed that the number of TCR molecules on the T-cell surface of SLE patients is lower than normal condition, and otherwise for these receptors CD molecules make specific connection. SLE phenotypes are characterized by double CD negativity (CD3 +/À , CD4 À ) caused by an abnormal level of IL-2 and IL-17.…”
Section: Immunophenotypingmentioning
confidence: 99%